The role of Anaesthesiologists at Different Levels of Difficult Airway Management Care - A Case Report: A precarious definitive airway - Pacheco, Marta; Castro, Rita; Aguiar, José; Órfão, Jorge (Journal of the Portuguese Society of Anesthesiology, 2022)
Mucopolysaccharidoses are a group of lysosomal storage diseases. The deficiency of specific lysosomal enzymes leads to accumulation of glycosaminoglycans (GAGs) in the tissues and organs. Patients had Difficult Airway (DA) criteria: long epiglottis, anterior larynx, small trachea, short neck, temporo-mandibular joint rigidity, cervical instability and complications with difficult ventilation and oxygenation. We describe a case that illustrates the role of the anaesthesiologist in the approach and maintenance of a DA during the disease progression. DA criteria made the maintenance of spontaneous ventilation a primary goal and fiberoptic should be the first approach. A precarious definitive airway and previous respiratory arrest linked to infraglotic obstruction, made manipulation of the tracheostomy cannula stressing, dangerous and not definitive. Trained anaesthesiologists in DA, fiberoptic and FROVA allowed safe diagnosis and exchange the cannula safely.